2015
DOI: 10.1080/11356405.2015.1006847
|View full text |Cite
|
Sign up to set email alerts
|

School adjustment among Spanish adolescents: influence of parental socialization / El ajuste escolar en los adolescentes españoles: influencia de la socialización parental

Abstract: The values and attitudes toward education that parents transmit to their children considerably affect their school adjustment. The aim of this study was to analyse the relationships between academic adjustment in Spanish adolescents and parental socialization styles. Participants in the study were 487 adolescents (53.9% females) between 12 and 14 years old (M = 13.13, SD = 0.79). Based on their responses on a parental socialization scale, families were classified according to the classic four parenting styles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 62 publications
10
29
0
18
Order By: Relevance
“…The ESPA29 theoretical structure was confirmed in studies conducted in Spain (Musitu and García, 2001), Brazil (Martínez et al, 2011, 2012) and the United States (Martínez et al, 2017) showing an invariant pattern for adolescent males and females. This scale has been utilized in a great many studies to consistently relate parenting with other variables (e.g., Martínez and García, 2007; Gracia et al, 2012; Martínez et al, 2013; Fuentes et al, 2015a,b). It is remarkable that the ESPA29 parenting acceptance/involvement dimension has been related to high adolescents' self-concept, and the strictness/imposition dimension has been related to low adolescent self-concept (e.g., Fuentes et al, 2011a,b; García and Gracia, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESPA29 theoretical structure was confirmed in studies conducted in Spain (Musitu and García, 2001), Brazil (Martínez et al, 2011, 2012) and the United States (Martínez et al, 2017) showing an invariant pattern for adolescent males and females. This scale has been utilized in a great many studies to consistently relate parenting with other variables (e.g., Martínez and García, 2007; Gracia et al, 2012; Martínez et al, 2013; Fuentes et al, 2015a,b). It is remarkable that the ESPA29 parenting acceptance/involvement dimension has been related to high adolescents' self-concept, and the strictness/imposition dimension has been related to low adolescent self-concept (e.g., Fuentes et al, 2011a,b; García and Gracia, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…From the positive psychology perspective, in a community sample of adolescents, it was revealed that the most contributing factor to increase the subjective well-being is family self-concept (González-Carrasco et al, 2017). Finally, parenting studies analyzing the influence of parental practices on self-concept in Spain (Fuentes et al, 2015b; Riquelme et al, 2018), other European (Calafat et al, 2014) and Latin-American countries (Peru, Bustos et al, 2015; Carranza and Bermúdez-Jaimes, 2017; Brazil, Martínez et al, 2007; Martínez and García, 2008), and also in the United States (García et al, 2013), have shown that parenting characterized by the use of acceptance and involvement practices is associated with higher levels of self-concept, in several dimensions, than parenting characterized by the use of practices of strictness and imposition (Fuentes et al, 2011a,b; Martínez-González et al, 2016; Martínez et al, 2017, 2019). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ESPA29 has been widely used in Spain (Martínez and García, 2007; García and Gracia, 2009, 2010; Martínez et al, 2013; Fuentes et al, 2015a,b,c) and also in Portugal (Rodrigues et al, 2013) in order to study the relations between socialization styles and different adolescent adjustment variables. These studies have also measured parenting styles congruently and point out the importance of the practices of the acceptance/involvement dimension in adolescent adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Errendimendu akademikoari dagokionez, eskola-doikuntzaren adierazlea izaki, ikerketa ugaritan egiaztatu da aipatu errendimendua handiago dela nesketan (Antonio-Agirre et al, 2015;Droguett, 2011;Fuentes, Alarcón, Gracia, eta García, 2015;Heras eta Navarro, 2012;Ibabe, 2016), motibazio handiagoa erakutsi eta ikasketetan denbora gehiago ematen dutelako (Hernando et al, 2013). Gainera, hainbat ikerketaren arabera, generoak errendimendu akademikoan du eragina; neskek errendimendu hobea dute ahozko ezagutzen arloetan (Costa eta Tabernero, 2012) eta mutilek, berriz, zientzietan eta matematiketan (González-Pienda et al, 2012Suá-rez-Álvarez et al, 2014).…”
Section: Desberdintasunak Sexuaren Araberaunclassified
“…Integrazioaren ildotik, beste behin ere neska nerabeek puntuazio altuagoak lortzen dituzte eta mutilek, berriz, eskolan integratzeko arazo gehiago (Antonio-Agirre et al, 2015;Droguett, 2011;Heras eta Navarro, 2012), jokaera disruptibo gehiago (Fuentes et al, 2015), biktimizazio eta jokabidearazo gehiago erakusten dituzte (Liu, Lan, Hsu, Huang, eta Chen, 2014). Gainera, mutilek indarkeria handiagoa erabiltzen dutela erakutsi da (Povedano, Estévez, Martínez, eta Monreal, 2012;Shao, Liang, Yuan, eta Bian, 2014), baita eraso zuzena, ahozkoa eta fisikoa ere (Heras eta Navarro, 2012); gainerako kideek sarriago baztertzen dituztela ere frogatu da (Cava eta Musitu, 1999a (18)(19)(20); gaztaroan edo heldutasun goiztiarrean, berriz, 21-40 urte bitarteko adin-tartea barne hartzen da (Feldman, 2007).…”
Section: Desberdintasunak Sexuaren Araberaunclassified